2018
DOI: 10.2147/idr.s180254
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics and comparative genomics analysis of a clinical <em>Enterococcus casseliflavus</em> with a resistance plasmid

Abstract: PurposeThe aim of this work was to investigate the molecular characterization of a clinical Enterococcus casseliflavus strain with a resistance plasmid.Materials and methodsEn. casseliflavus EC369 was isolated from a patient in a hospital in southern China. The minimum inhibitory concentration was found by means of the agar dilution method to determine the antimicrobial susceptibilities of the strains. Whole-genome sequencing and comparative genomics analysis were performed to analyze the mechanism of antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…had the highest 16S rRNA gene sequence similarity (100%) to Enterococcus casseliflavus , Enterococcus gallinarum , and Enterococcus saccharolyticus . A recent study reported that E. casseliflavus with a resistance plasmid shows resistance to erythromycin, kanamycin, and streptomycin . Thus, antibiotic dependence and independence of plastic biodegradation relies on the antibiotic resistance genes in the core gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…had the highest 16S rRNA gene sequence similarity (100%) to Enterococcus casseliflavus , Enterococcus gallinarum , and Enterococcus saccharolyticus . A recent study reported that E. casseliflavus with a resistance plasmid shows resistance to erythromycin, kanamycin, and streptomycin . Thus, antibiotic dependence and independence of plastic biodegradation relies on the antibiotic resistance genes in the core gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that E. casseliflavus with a resistance plasmid shows resistance to erythromycin, kanamycin, and streptomycin. 32 Thus, antibiotic dependence and independence of plastic biodegradation relies on the antibiotic resistance genes in the core gut microbiome.…”
Section: Plastic Biodegradation and Depolymerizationmentioning
confidence: 99%
“…The transfer of a plasmid containing antimicrobial resistance genes often occurs in Enterococcus spp. and plays an important role in dissemination of drug resistance genes (Zheng et al, 2009; Yin et al, 2018). Previously, many linear plasmids have been reported, especially in Streptomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical threat of non-faecium and non-faecalis enterococci has been often underestimated because they do not cause frequent infections (27,28); however, non-faecium and non-faecalis enterococci have the potential to cause outbreaks of infection (29). Moreover, they might become important reservoirs of vancomycin resistance genes (13).…”
Section: Figmentioning
confidence: 99%